1973
DOI: 10.1128/aac.4.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships Among the Aminoglycoside Antibiotics: Role of Hydroxyl and Amino Groups

Abstract: The close structural similarity of several of the deoxystreptamine-containing aminoglycoside antibiotics (gentamicins, neomycins, kanamycins, tobramycin) and the recent isolation of enzymatically N-acetylated aminoglycosides have permitted a systematic comparison of the structure-activity relationships in this group of antibiotics. The number and location of amino groups on the hexoses and the site of attachment of the other rings to deoxystreptamine have been shown to exert a profound effect on the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 12 publications
4
56
0
1
Order By: Relevance
“…It stimulated misreading of poly(U) in yeast cell free extracts (Benveniste and Davies 1973;Palmer et al 1979;Singh et al 1979) and induced phenotypic suppression of both nonsense and missense mutations in yeast (Palmer et al 1979;Singh et al 1979). Paromomycin binds to a region of helix 44 (h44) of the small ribosomal subunit (Carter et al 2000) and this binding is thought to increase misreading by inducing a structural change in the decoding center similar to that induced by the binding of a cognate tRNA (for review, see Ogle et al 2003), thereby altering the kinetics of decoding to increase the probability of acceptance of near-cognate tRNAs in the A site (Pape et al 2000).…”
Section: The Aminoglycoside Antibiotic Paromomycin Increases a Subsetmentioning
confidence: 99%
“…It stimulated misreading of poly(U) in yeast cell free extracts (Benveniste and Davies 1973;Palmer et al 1979;Singh et al 1979) and induced phenotypic suppression of both nonsense and missense mutations in yeast (Palmer et al 1979;Singh et al 1979). Paromomycin binds to a region of helix 44 (h44) of the small ribosomal subunit (Carter et al 2000) and this binding is thought to increase misreading by inducing a structural change in the decoding center similar to that induced by the binding of a cognate tRNA (for review, see Ogle et al 2003), thereby altering the kinetics of decoding to increase the probability of acceptance of near-cognate tRNAs in the A site (Pape et al 2000).…”
Section: The Aminoglycoside Antibiotic Paromomycin Increases a Subsetmentioning
confidence: 99%
“…Neomycin B inhibits translation at the prokaryotic ribosome by inducing misreading of the genetic code (Davies et al+, 1965;Davies & Davis, 1968)+ Furthermore, several aminoglycosides inhibit the catalytic activity of self-splicing group I introns and of the hammerhead and HDV ribozymes in vitro (von Ahsen et al+, 1991;Stage et al+, 1995;Rogers et al+, 1996)+ Two RNA-protein interactions in HIV, RRE-Rev and TarTat, are disrupted by neomycin B in vitro (Zapp et al+, 1993;Mei et al+, 1995)+ Detailed analyses of neomycin binding sites have revealed two types of RNA target sites for aminoglycoside antibiotics+ The first type contains internal asymmetrical loops with widened major grooves, which are found in the decoding site of the 16S rRNA (Noller, 1991;Purohit & Stern, 1994;Fourmy et al+, 1996;Recht et al+, 1996), in the RRE RNA of HIV (Zapp et al+, 1993), in the P4/P5 internal loop of group I introns (von Ahsen & Noller, 1993;Cate et al+, 1996;Hoch et al+, 1998), and in several neomycin aptamers isolated via in vitro selection (Wallis et al+, 1995)+ The second type of target sites are divalent metal ion binding sites in the core of ribozymes (Clouet d'Orval et al+, 1995;Rogers et al+, 1996;Hoch et al+, 1998)+ Molecular-dynamics-simulation experiments revealed that the distances between positively charged aminogroups of aminoglycosides coincide with the distances of several divalent metal ions in the X-ray structure of the hammerhead ribozyme+ This leads to the proposal that neomycin B acts via simultaneous displacement of several essential metal ions (Hermann & Westhof, 1998)+ The inhibitory neomycin binding site in the T4 phage td intron was shown to be a type-two binding site (Hoch et al+, 1998)+ Inhibition of translation and disruption of the RRERev interaction by neomycin B has been demonstrated to occur both in vitro and in vivo (Benveniste & Davies, 1973;Zapp et al+, 1993)+ While the concentrations of neomycin B required to inhibit translation are similar in vivo and in vitro, disruption of the RRE-Rev interaction required almost 100-fold higher concentrations in vivo than in vitro+ These observations suggest that aminoglycoside binding might differ substantially depending on the intracellular conditions+ Here we examined the effects of neomycin B and several other aminoglycosides on splicing of the td intron in vivo+…”
Section: Introductionmentioning
confidence: 99%
“…However, Table 4 clearly indicates that 3-N derivatives are not substrates for AAC (3). These results suggest strongly that the presence and the activity of AAC(3) in E. coli R11 and Serratia marcescens 22522 are not sufficient to explain the resistance of these bacteria to tobramycin.…”
Section: Discussionmentioning
confidence: 56%